The effects of nanoSiO2 on the properties of fresh and hardened cement-based materials through its dispersion with silica fume. (1st September 2017) - Cai, Yamei; Hou, Pengkun; Cheng, Xin; Du, Peng; Ye, Zhengmao
Highlights: The dispersion and distribution of NS was tailored by SF. The pre-adsorption of NS on SF helped increasing the fluidity of mortar. The coating effects of NS on cement hydration was mitigated with the help of SF. Abstract: The dispersion/distribution of nanoSiO2 in cement-based materials is known as very influential on the property gain, but still remains a big problem that has not been well addressed. The aim of this work was trying to tailor the dispersion/distribution of nanoSiO2 in cement-based materials with silica fume. Firstly, the surface of silica fume was amino-functionalized (AFSF) for adsorbing and dispersing nanoSiO2 (NS), then the adsorption of NS on AFSF and its effects on the properties of fresh and hardened cement-based materials were studied. Results showed that the adsorption of NS on AFSF followed the Freundlich adsorption model, and a multi-layer adsorption characteristic were found. The adsorption of NS on AFSF helped increasing the fluidity of mortar, and mitigated the negative effects of nanoSiO2 on the hydration and hardening properties of cement-based materials at late ages, resulting in an improved compressive strength, a higher degree of hydration of cement and a compacter microstructure at late ages than the pure AFSF-added sample, and a higher and comparable compressive strength than the control sample at the early and late age can be resulted. It can be suggested from this work that the dispersion/distribution of nanomaterial in cement-based materials with silica fume helps a better exploration of the nano-modification of cement-based materials and provide a new technique on producing nano-modified cement concrete, and work on making good absorption of nanomaterial on SCM is worth of further study.